2019
DOI: 10.3897/zookeys.835.33166
|View full text |Cite
|
Sign up to set email alerts
|

New species of leaf-mining Phyllonorycter (Lepidoptera Gracillariidae) from Siberia feeding on Caragana (Fabaceae)

Abstract: During a DNA barcoding campaign of leaf-mining Gracillariidae from the Asian part of Russia, a new species ofPhyllonorycterHübner, feeding on the Siberian pea shrub,CaraganaarborescensLam. (Fabaceae) was discovered in Siberia. Here, this taxon is described asPhyllonorycterivanisp. n.Among Fabaceae-feedingPhyllonorycter, so far onlyP.caraganella(Ermolaev) has been known to develop onCaragana.PhyllonorycterivaniandP.caraganellashow a large divergence in morphology (external and male genitalia) and barcode region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The current study observed the growth and development of plants according to the method of [BEIDEMAN 1974;MINEA et al 2018;NORELDIN et al 2015] using "Recommendations for the study of the ontogenesis of introduced plants in the botanical gardens of the USSR" [SYKURA, SYRYTSA 1990]. The current study determined the productivity of raw material and seeds according to "Research methodology for the introduction of medicinal plants"; the current study also used methods adopted in other botanical gardens [KIRICHENKO et al 2019;KLUBNIKIN et al 2000;MININA 2020], with slight modifications appropriate for the local conditions. Thus, from the entire array of phenological data, only the main indicators characterizing the annual ontogenetic cycle were visually determined: the beginning and end of the growing season, flowering and seed ripening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study observed the growth and development of plants according to the method of [BEIDEMAN 1974;MINEA et al 2018;NORELDIN et al 2015] using "Recommendations for the study of the ontogenesis of introduced plants in the botanical gardens of the USSR" [SYKURA, SYRYTSA 1990]. The current study determined the productivity of raw material and seeds according to "Research methodology for the introduction of medicinal plants"; the current study also used methods adopted in other botanical gardens [KIRICHENKO et al 2019;KLUBNIKIN et al 2000;MININA 2020], with slight modifications appropriate for the local conditions. Thus, from the entire array of phenological data, only the main indicators characterizing the annual ontogenetic cycle were visually determined: the beginning and end of the growing season, flowering and seed ripening.…”
Section: Methodsmentioning
confidence: 99%
“…The use of valuable plant species and their products in various sectors of the economy including the pharmaceutical industry requires a wider and more comprehensive study of the possibility of cultivating plants in new areas [MININA 2020]. Unlike mass-produced crops, medicinal plants require different soil and climatic conditions, necessitating the study of their characteristic features and the development of methods of industrial cultivation [KIRICHENKO et al 2019;KLUBNIKIN et al 2000;RAO, RAVISHANKAR 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Gracillariidae species have been discovered and described by the following authors: e. Meyrick (about 600 species), T. Kumata (nearly 160), L. Vári (more than 100 species); many others having described more than 50 species each (e.g., Lord Walsingham, A. F. Braun). About 30 new species have also been described by authors from Russia (Gerasimov 1930(Gerasimov , 1931(Gerasimov , 1933Kuznetzov 1960Kuznetzov , 1975Kuznetzov , 1979aKuznetzov , 1979bermolaev 1977, 1986Kuznetzov & Baryshnikova 2000, 2001Kirichenko et al 2018Kirichenko et al , 2019. Recently, some interesting research data, including numerous descriptions of new species, were published from the Afrotropical region by Jurate De Prins (De Prins & Kawahara 2012), from China by numerous researchers (e.g., Liu & Yuan 1990;Bai & Li 2009;Zhang et al 2012;Bai et al 2015Bai et al , 2016Li et al 2015;Li & Zhang 2016;Liu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among these insects are, for example, species belonging to the genera Caloptilia, Callisto, Cameraria, Macrosaccus, Micrurapteryx, Parornix, Parectopa, or Phyllonorycter (Csóka et al 2009 Kirichenko et al 2019a, b, c). Nevertheless, in spite of their great importance, particularly in the context of increasing invasion records, they have been largely unexplored, and new species are still being found (Davis and De Prins 2011;Kirichenko et al 2019b).…”
Section: Introductionmentioning
confidence: 99%